Experimental Study on the Seismic Behavior of CFST Self-Centering Rocking Bridge Piers - Wei Lu; Yu Zou; Xingyu Luo; Jun Song; Haiqing Li (Buildings)
Compared to conventional reinforced concrete (RC) piers, self-centering rocking piers exhibit better seismic resilience and sustain minor damage. However, their construction typically relies on prefabrication. Moving large, prefabricated components can be challenging in mountainous areas with limited transportation access. Therefore, using concrete-filled steel tube (CFST) piers is a practical alternative. The steel tube both serves as a construction permanent formwork and enhances the compressive performance of concrete through confinement effects. To apply CFST self-centering rocking piers in mountainous regions with high seismic intensity, a fast construction system was designed and a 1:4 scale specimen was developed for testing. Lateral cyclic loading tests revealed that the specimen exhibited good deformation and self-centering capabilities, with a residual drift ratio of only 0.17% at a drift ratio of 7.7%. Most of the horizontal displacement was contributed through a rocking gap opening, resulting in minimal damage to the pier itself. The damage was concentrated primarily in the energy-dissipating rebars, while the prestress strands remained elastic, though prestress loss was observed.